(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2012)
World consumers are looking for personal care products that supply multiple benefits with minimal efforts. They also expect the latest technology advances to be incorporated into innovative formulations. The trend toward therapeutic cosmetics will lead to a better understanding of modern ingredients and their assessment techniques. To obtain skin care formulations with real consumer-perceivable benefits and to optimize sensory attributes, formulators are resorting to technology that until recently was exclusively used in cosmetic products. Various formulations comes under special delivery systems like Vesicular, Particulate systems, emulsions type Particulate type and other delivery systems along with their applications are shown in this article, as it results in an economic uplift of cosmetic industry in various parts of the world. Little evidence is seen that nanoparticles in cosmetics and sunscreen might be a problem at this time and its need is further explored for a better understanding of these novel technologies. Thus, novel cosmaceutical delivery systems reviewed here possess enormous potential as next-generation smarter carrier systems.